2007
DOI: 10.1007/s15010-007-6194-9
|View full text |Cite
|
Sign up to set email alerts
|

“Recreational” Drug Abuse Associated with Failure to Mount a Proper Antibody Response after a Generalised Orthopoxvirus Infection

Abstract: Infections with orthopoxviruses usually lead to cross-protection among all species of the family. This has been a prerequisite for successful eradication of smallpox. Here we report the rare case of a 17-year-old male, who survived a generalised cowpox virus infection of unusual severity but surprisingly did not show a proper seroconversion. Only a very weak antibody production was observed in early and late serum samples, which initially appeared to be cowpox virus specific in immunofluorescence. No neutralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Prolonged marijuana use is associated with immune-suppression (Klein et al , 2003; Klein and Cabral, 2006) and chronic cannabis use has been reported to result in failure to mount an appropriate immune response to certain viruses (Huemer et al , 2007). Such effects on the immune system produced by Δ 9 -THC has been suggested to occur via activation of CB 2 Rs (McKallip et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged marijuana use is associated with immune-suppression (Klein et al , 2003; Klein and Cabral, 2006) and chronic cannabis use has been reported to result in failure to mount an appropriate immune response to certain viruses (Huemer et al , 2007). Such effects on the immune system produced by Δ 9 -THC has been suggested to occur via activation of CB 2 Rs (McKallip et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In immunomodulation of cannabinoids in viral infections where viral replication is sensitive to the anti‐viral responses, activation of CB receptors increases progression of the disease by inhibition of immune anti‐viral responses. For example; viral infection by orthopoxvirus [Huemer et al, ], vaccinia [Huemer et al, ], HCV [Sun et al, ], HSV‐1 [Fischer‐Stenger et al, ], HSV‐2 [Cabral et al, 1987], Kaposi's sarcoma‐associated herpes virus [Zhang et al, ], HIV, and feline leukemia [Wang and Ho, ] increases during CB receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…In HCV infections, clinical studies have shown a profound co-morbidity of recreational cannabinoid use, for disease progression [54,56]. One case report of Cowpox infection, a very rare human pathogen, indicated that recreational use of cannabinoids was associated with generalized infection and very poor immune responses to the virus [40]. …”
Section: Discussionmentioning
confidence: 99%